Quality testing of mifepristone and misoprostol in 11 countries - Bower, Jason; Chinery, Lester; Fleurent, Alessandra; Gülmezoglu, A. Metin; Im‐Amornphong, Wallada; Kilfedder, Catherine; Procter, Petra; Tomazzini, Alessandra (John Wiley & Sons, Ltd, 2024)
Previous studies have demonstrated quality concerns with misoprostol. Mifepristone, however, has not been extensively assessed for quality. Between 2020 and 2021, Concept Foundation and the International Planned Parenthood Federation conducted a study to determine the quality of these medical abortion drugs in low- and middle-income countries (LMIC). The collection of batch samples of misoprostol and mifepristone was carried out by trained sampling agents in selected LMIC. Single drug packs and combipacks were sampled. A World Health Organization prequalified laboratory conducted testing method verifications and subsequent sample analysis. Tests included identification, assay, related substances, and content uniformity for misoprostol, and identification, assay, related substances, and dissolution for mifepristone. Samples were collected from Burkina Faso, Cambodia, Democratic Republic of Congo, India, Kyrgyzstan, Moldova, Nepal, Nigeria, Pakistan, Uganda and Vietnam. Sixty-four pooled batch samples were tested, consisting of 31 combipacks, 26 misoprostol-only and seven mifepristone-only products. Overall, 54.7% of samples were non-compliant with one or more of the specifications, representing 51.6% of combipack products, 57.1% of misoprostol tablets analyzed and 23.7% of mifepristone tablets. One falsified misoprostol-only product was found. The present study confirms that a significant problem still exists in relation to the quality of medical abortion drugs in LMIC. For misoprostol, our findings suggest that historical concerns around primary packaging may have been largely resolved but that manufacturing processes for both finished product and active pharmaceutical ingredient need to be improved. The present study also provides evidence of mifepristone quality issues.
Keywords: falsified medicine, medical abortion, medicine quality, mifepristone, misoprostol, pharmaceutical analysis, quality survey, substandard medicine